Rola Gruzji w polityce zagranicznej Stanów Zjednoczonych w XXI w. - Andrzej Kozłowski (Ksiegarnia Akademicka Publishing, 2014)
Georgia and the United States play in the international area complete different roles. Georgia is a small Caucasian country with limited potential, which could not rather play a crucial role in the foreign policy of the United States – the global actor with interests all over the world. Indeed, this situation took place in 90s. However, the beginning of 21st century and assuming the office of president by George W. Bush changed the position of this country and Georgia started to become more and more important in America foreign policy. The situation shifted when Barack Obama became a president in 2009. Since that time Georgia’s position in American foreign policy started to decrease. The last crisis, which happened in Ukraine and the worsening in relations between the United States and Russia may change the significance of Georgia. The main thesis of this article claims that the role and position of Georgia depend on changing interests of the United States in South Caucasus and Central Asia regions.